PERAN DINAS PENDIDIKAN DALAM MENINGKATKAN MUTU PENDIDIKAN DI KABUPATEN MANDAILING NATAL - Harahap, Salma; Inkrid Alia; Muhammar Fuadi; Rodiyah; Rosdanilah; Siti Masitoh; Ilham Ramadhan Siregar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of the Mandailing Natal Regency Education Office in improving the quality of education in the region. The primary problem in this study relates to the local government's efforts to manage, foster, and supervise educational units to improve the quality of educational services, which still face various challenges both in terms of resources and regional conditions. The study used a qualitative approach with descriptive methods to obtain a comprehensive picture of the institution's role. Data collection techniques included observation, interviews, and documentation with parties involved in the provision of education. The data obtained were then analyzed through the stages of data reduction, data presentation, and conclusion drawing.The results indicate that the Mandailing Natal Regency Education Office plays a strategic role as a policy formulator, program implementer, facilitator, and evaluator in efforts to improve the quality of education. Various programs implemented include improving teacher competency through training and workshops, equalizing educational facilities and infrastructure, implementing academic and managerial supervision, and strengthening internal quality assurance systems in schools. Furthermore, the Education Office also builds collaborations with various parties to support the improvement of the quality of educational services. However, the program's implementation still faces several challenges, including budget constraints, uneven distribution of teaching staff, and challenging geographic conditions. Therefore, more comprehensive planning, strengthened coordination between stakeholders, and optimized resource utilization are needed to ensure sustainable improvements in education quality.